Effect of interval time between hysterosalpingography and intrauterine insemination on the pregnancy outcome of infertile patients - Ling, Li; Chen, Mengzhu; Shen, Tao; Yang, Fang; Jin, Yihan; Liang, Yuanjiao (Frontiers in Endocrinology, 2023)
Background: Hysterosalpingography (HSG) is the most commonly applied tubal patency test in clinical practice. Although some studies have found an increased pregnancy rate after HSG, no studies to date have specifically characterized the effect of interval time between HSG and IUI on pregnancy outcome. Objectives: To investigate the effect of interval time between HSG and intrauterine insemination (IUI) on live birth rates of infertile patients. Methods: Retrospective cohort study. The reproductive medical record system was used to identify patients who completed ≥1 IUI cycle between January 2017 and October 2021. According to the interval time between HSG and IUI, patients were divided into three groups: <6months interval group,6-12 months interval group and ˃12 months interval group. The generalized estimating equation with Poisson distribution was used to estimate the risk ratios (RRs) and 95% confidence intervals (CIs) of different groups. Results: A total of 413 patients completed 701 IUI cycles during the study period, <6months interval group, 415 cycles; 6-12 months interval group, 138 cycles; ˃12 months interval group, 148 cycles. The live birth rate of <6 months group was higher than other two groups (17.35 % vs. 12.32% vs. 8.11%, P=0.017); Similarly, the clinical pregnancy rate of <6 months group was also higher than other two groups (19.76 % vs. 14.49% vs.11.49%, P=0.049). When adjusted separately for FSH, AMH, infertility type, duration of infertility, infertility diagnosis, total motile count (TMC) of sperm, medications, endometrium size and dominant follicle size, the live birth rate of ˃12 months group severally significantly decreased by 60% (ajusted RR = 0.40, 95% CI [0.19–1.40]). The cumulative clinical pregnancy and live birth rates of <6 months group were higher than other two groups (P<0.05), but the cumulative pregnancy rate among three groups were not statistically differnet (log rank test: P=0.06). Conclusion: The interval time between hysterosalpingography and IUI is related to pregnancy outcome. The clinical pregnancy and live birth rates were the highest when the time interval was less than 6 months. Therefore, IUI should be recommend as soon as possible after HSG if the patient couple meets the IUI indication.